"How to Do Things With Words": Mechanisms Bridging Language and Action in Management Research. (January 2019) - Lockwood, Christi; Giorgi, Simona; Glynn, Mary Ann
We review the past quarter century of literature linking language and action in management research published from 1993 through 2017. Different from recent in-depth reviews that focus narrowly on particular forms that words take, we look across these different kinds of word assemblages to uncover broad themes and mechanisms that link words with action outcomes in organizational settings. Classifying common conceptual approaches and prominent outcomes, we systematize and synthesize existing work on how to do things with words, identifying points of tension or contradiction as well as consistencies or overlaps across areas of research and methodologies. In addition, we go beyond typologies of how words are constructed to unearth how words function in the service of action; in so doing, we articulate three underlying mechanisms that connect words to action—resonance, enactment, and power—and discuss each. We end with a discussion of promising avenues for future research.